2006
DOI: 10.1002/app.24604
|View full text |Cite
|
Sign up to set email alerts
|

Suspension copolymerization of styrene and divinylbenzene: Formation of beads

Abstract: Suspension copolymerization of styrene and divinylbenzene (DVB) was carried out using benzoyl peroxide as initiator and magnesium hydroxide as suspending agent in water at 80°C under nitrogen atmosphere to produce styrene-DVB copolymer beads. These beads were characterized by infrared spectroscopy, thermal gravimetric analysis, and scanning electron microscopy. Porosity generated in styrene-DVB copolymer beads by incorporation of solvents in the polymerization system was confirmed by SEM micrograph, apparent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…In fact, as we observed from the low-magnification picture (Fig. 4), spherical particles were detected with the diameter-around 10 lm; the same morphology has been previously reported in literature in SEM analyses of anionic resins similar to those used at the end of the restoration work (Gupta et al 2006;Albuszis et al 2016).…”
Section: Chemical Analyses and Sem Observationsupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, as we observed from the low-magnification picture (Fig. 4), spherical particles were detected with the diameter-around 10 lm; the same morphology has been previously reported in literature in SEM analyses of anionic resins similar to those used at the end of the restoration work (Gupta et al 2006;Albuszis et al 2016).…”
Section: Chemical Analyses and Sem Observationsupporting
confidence: 89%
“…4), spherical particles were detected with the diameter-around 10 lm; the same morphology has been previously reported in literature in SEM analyses of anionic resins similar to those used at the end of the restoration work (Gupta et al 2006;Albuszis et al 2016). Some representative microsamples from the fresco were observed by SEM, at higher magnifications, and confirmed the absence of micro-organisms after the treatment with the anionic resin and the large presence of spherical particles.…”
Section: Chemical Analyses and Sem Observationsupporting
confidence: 83%
“…A profound relationship was observed between the concentration of catalyst and yield%. We observed a direct proportionality between the concentration of catalyst and % yield of the polymeric beads, which was found in accordance with the facts reported by Gupta et al28 During the polymerization process, concentration of catalyst was varied from 1.68 to 10.13 wt %. As shown in Figure 5, when the concentration of catalyst was initially 1.68 wt %, the yield was 3.19% only.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, poly(styrene-co-divinylbenzene) was widely used as a solid-support. Gupta et al [41] reported the surface area of 79 m 2 /g for a poly(styreneco-divinylbenzene). Our published work reported much higher surface area which is above 500 m 2 /g using 1,2-dichlorobenzene as a solvating porogen [14,42].…”
Section: Free-radical Polymerizationmentioning
confidence: 99%